Do loyalty cards enhance loyalty? a study in the Portuguese pharmaceutical sector - Marques, S.; Lindeza, A.; Cardoso, M. (The Portuguese Marketing Conference 15 Proceedings, 2015)
The primary goal of the investigation is to analyze the influence of the “Portuguese Pharmacies card” (PP card) on the pharmacies’ customers behaviour. It also intends to examine whether marketing stimuli influence consumers’ buying behavior with regard to non-prescription medicines / health and wellness product / pharmaceutical services (NP/HW/PS) and to understand if the consumer social-demographic characteristics influence purchase decisions and customers’ loyalty. The research results are provided by the responses to a survey of 385 clients of Portuguese pharmacies, over 18 years of age, resident in Lisbon Metropolitan Area. 57% of these respondents are female, 70% are between 35 and 64 years and 80% earn a net monthly income of the household equal or greater than 1001€. When compared with the target population, it turns out that there is an over-presence of respondents with secondary education, post-secondary and higher in the sample. More than half of respondents (59%) already adhered to the Portuguese Pharmacies card which implies that all purchases made by their families (except prescription drugs) are worth points that may be redeemed for specific products or coupons to be used in pharmacy. The main reason for joining the card relates to the fact that respondents “usually attend a Portuguese pharmacy” (38.8%), followed by the fact that they consider that “there are several advantages associated with use of the card” (25.6%) and “can rebut the points for several NP/HW/PS (18.1%). Most of those who did not join the card (37%) are unaware of it and 16% think the advantages do not justify the engagement. The results of the investigation demonstrate that the use of the PP card is clearly influenced by the consumer social demographic characteristics. For example: 77% of those who joined the card are women and 67% of those who did not adhere are men (a significant association). The Marketing of stimuli considered in this research include four communication tools: advertising, sales promotions, word of mouth and the sales force. According to the results obtained, the degree of influence attributed to these various communication tools in the buying decision does not differ significantly in terms of socio-demographic categories. On the other hand, the purchase volume of NP/HW/PS is significantly dependent on the influence of advertising and sales promotions in the purchase decision. Furthermore, impulse buying of NP/HW/PS is significantly dependent on the influence of advertising, promotions and WOM. Subscribers of PP card are generally quite satisfied with it and rely on the card. As to the consumer buying behavior, it is found that only 14.1% of respondents are willing to exchange a NP/HW/PS by a similar product to accumulate more card points, which indicates that the vast majority are loyal to brands. It is also found that only 10.1% buys NP/HW/PS which had no intention of purchase, to accumulate points; and 28.2% buys a NP/HW/PS in larger quantities, in order to accumulate more points. We conclude that the Portuguese Pharmacies card indeed contributes to customer loyalty in the establishments where it is present. In order to meet customer expectations, a loyalty program should be adjusted over time, seeking to stimulate the satisfaction and reliance in this program.